Concern for the second generation: the case of the SNPJ – a cultural investment for the maintenance of the Slovene identity in the United States - Milanič, Irena (Two Homelands, 2001)
The paper discusses how the Slovenska narodna podporna jednota – Slovene National Benefit Society tried to attract and involve the young members in its organization. The SNPJ started officially admitting juvenile members in 1913, while the monthly youth magazine Mladinski list–Juvenile was first published in July 1922. The first editor was Jakob Zupančič who was followed in 1926 by Andrej Kobal. From 1929 to 1944 the magazine was edited by Ivan Molek. 1938 is an important year because the Juvenile Circles started to be organized. The magazine Mladinski list–Juvenile assumed the important role of creating connections between the scattered youth clubs throughout the American territory. The paper discusses how the Slovenska narodna podporna jednota – Slovene National Benefit Society tried to attract and involve the young members in its organization. The SNPJ started officially admitting juvenile members in 1913, while the monthly youth magazine Mladinski list–Juvenile was first published in July 1922. The first editor was Jakob Zupančič who was followed in 1926 by Andrej Kobal. From 1929 to 1944 the magazine was edited by Ivan Molek. 1938 is an important year because the Juvenile Circles started to be organized. The magazine Mladinski list–Juvenile assumed the important role of creating connections between the scattered youth clubs throughout the American territory.